2013
DOI: 10.1007/s11102-013-0524-y
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea in patients with prolactinoma before and after treatment with dopamine agonists

Abstract: The OSA prevalence in patients with prolactinoma is similar to the obese subjects and did not change after treatment. Higher BMI and visceral obesity, but not prolactin levels, seem to be the major factor involved in the occurrence of OSA in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 27 publications
2
33
0
1
Order By: Relevance
“…Obstructive sleep apnea (OSA) is a common comorbid condition in various skull base tumors, including functioning pituitary adenomas . Among the functioning pituitary adenomas, 34% and 46% of patients with prolactinoma and corticotropinoma were found to have OSA, respectively .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Obstructive sleep apnea (OSA) is a common comorbid condition in various skull base tumors, including functioning pituitary adenomas . Among the functioning pituitary adenomas, 34% and 46% of patients with prolactinoma and corticotropinoma were found to have OSA, respectively .…”
mentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a common comorbid condition in various skull base tumors, including functioning pituitary adenomas . Among the functioning pituitary adenomas, 34% and 46% of patients with prolactinoma and corticotropinoma were found to have OSA, respectively . Hormonal irregularities associated with functioning pituitary tumors contribute to obesity in some patients, putting them at risk for OSA …”
mentioning
confidence: 99%
“…This is consistent with the reported range in the literature for endoscopic CSF leak rates which varies from 0.5 to 14%. 1,4,8,11,12,[18][19][20]26,30,45 This suggests that patients with OSA are at minimally increased risk of leak compared with their unaffected counterparts. This may be due to greater use of advanced closure methods in this population; however, this was not reviewed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] OSA has also been established as an independent risk factor for spontaneous CSF leak. [14][15][16][17][18][19][20] OSA causes cerebral vasodilation due to periods of hypercapnia, which results in increased ICP, a phenomenon also found in OSA patients while awake. 16 The mainstay of treatment for OSA is positive pressure ventilation (PPV), usually in the form of continuous positive airway pressure (CPAP).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, lifestyle changes, including daily physical activity, improved sleep hygiene, and dietary adjustments improve not only metabolic syndrome, but also OSAS, especially in obese patients [6]. In obese subjects with prolactinoma, Barbosa et al described that OSAS prevalence is similar to the obese controls: weight and visceral obesity (and not prolactin levels) were the major factor involved in the occurrence of sleep disorders, indeed OSAS symptoms did not improve after dopamine-agonist treatment [18]. Although adenotonsillar hypertrophy emerges as one of the major contributing factors to OSAS in children and adolescences than in adults, recently some authors reported that even obesity plays an important contributory role to the pathophysiology of OSAS in young subjects [19].…”
Section: The Round Trip Between Osas and Metabolic Syndromementioning
confidence: 99%